Antibiotic research and development: business as usual?. (10th February 2015) - Harbarth, S.; Theuretzbacher, U.; Hackett, J.; Adriaenssens, Niels; Anderson, James; Antonisse, Ad; Årdal, Christine; Baillon-Plot, Nathalie; Baraldi, Enrico; Bettiol, Esther; Bhatti, Taimur; et al.
Abstract : This article contends that poor economic incentives are an important reason for the lack of new drugs and explains how the DRIVE-AB intends to change the landscape by harnessing the expertise, motivation and diversity of its partners. Abstract: The global burden of antibiotic resistance is tremendous and, without new anti-infective strategies, will continue to increase in the coming decades. Despite the growing need for new antibiotics, few pharmaceutical companies today retain active antibacterial drug discovery programmes. One reason is that it is scientifically challenging to discover new antibiotics that are active against the antibiotic-resistant bacteria of current clinical concern. However, the main hurdle is diminishing economic incentives. Increased global calls to minimize the overuse of antibiotics, the cost of meeting regulatory requirements and the low prices of currently marketed antibiotics are strong deterrents to antibacterial drug development programmes. New economic models that create incentives for the discovery of new antibiotics and yet reconcile these incentives with responsible antibiotic use are long overdue. DRIVE-AB is a €9.4 million public–private consortium, funded by the EU Innovative Medicines Initiative, that aims to define a standard for the responsible use of antibiotics and to develop, test and recommend new economic models to incentivize investment in producing new anti-infective agents.